An evaluation of the strengthening of national behavior through developing and training of national non-commissioned officers of West Papua regional police - Simangunsong, Junus; Purnomo, Langgeng (REID (Research and Evaluation in Education), 2022)
The development of "Superior Human Resources, Advanced Indonesia" in the police institution through the transformation to the Republic of Indonesia Police (Polri) which is precise includes making superior police officers who have national behavior by strengthening the eleven values of national identity. To strengthen this national attitude, the West Papuan Regional Police Office conducted the development and training program for young non-commissioned officers (NCOs) from West Papua using the Experiential Learning (EL) approach for one month. From this activity, it is expected the participating NCOs will not only have a strong sense of national identity but also become police officers who have sociocultural competence as a state apparatus. This study aims to reveal the achievement of national behavior on the values of national identity according to the curriculum used by analyzing the correlation and factors that form national behavior. The data were collected using a questionnaire and through observation, interviews, and documentation, and were analyzed using quantitative and qualitative descriptive techniques. Before being used, the questionnaire and observation sheet readability was validated by officers and staff of the Indonesian National Police Headquarters, psychologists, and educational evaluation experts, resulting in a Cronbach Alpha value of 0.899. The research sample was 165 people, established using the simple random sampling technique, while for the acquisition of qualitative data, interviews were conducted with the Head of the National Police School, one observer, and one instructor. The results showed that the achievement of national behavior with the EL method approach had a Spearman Rank correlation of the eleven factors formed was >0.5 (0.853 and 0.853), and the factor analysis was able to summarize 62.10% of the eleven variables. This evaluation shows that the significant nature of the faith and mutual cooperation of the participants and the benefits have succeeded in increasing the behavior of the character of nationality in the category of inviting others.